PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA MATERI ANALISIS DATA MENGGUNAKAN MICROSOFT EXCEL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA - Nur Sa’ida Kismurdiani; Harits Ar Rosyid; Suparman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on enhancing students' creativity and learning outcomes through the implementation of the Culturally Responsive Teaching (CRT) approach in the topic of data analysis using Microsoft Excel in class VIII-J of SMP Negeri 19 Malang. The main problem faced by students is the low understanding of Informatics, particularly data analysis, which is often perceived as abstract and difficult to grasp. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of two cycles. Data were collected through observation and learning outcome tests. The results showed an improvement in student creativity from the